Preparation, formulation and deposition of mica flake supported cobalt oxide for nanostructured lithium ion battery anodes - Helmer, Alexandra; Rink, Anna; Esper, Julian Duane; Wu, Yanlin; Bachmann, Julien; Klupp Taylor, Robin (Advanced Powder Technology, 2019)
Abstract We describe the fabrication and morphological and electrochemical characterisation of lithium ion battery anodes whereby the active material is supported on flake-like microparticles. Using various physical analytical techniques we verify that nanostructured cobalt (II, III) oxide can be directly grown onto commercial titanium dioxide-coated mica flakes by a liquid phase oxidation route. We then investigate the formulation and deposition of this material along with carbon black in order to form electrodes. Here we consider two binder/solvent systems, one widely used based on polyvinylidene fluoride in N-methy-2-pyrrolidone, and one more recently identified based on sodium alginate in water. We show that the latter system is preferable for the formation of anodes using the cobalt oxide coated flake-like particles as it leads to a more homogeneous distribution of active and conductive material in the electrode. Using cyclic voltammetry and electrochemical impedance spectroscopy we show that this feature improves the access to active material and facilitates efficient charge transfer in the electrode while maintaining electrode integrity. Moreover, an electrode based on the alginate binder exhibited a high reversible specific capacity of 650 mAh/g along with 84.8% capacity retention after 70 cycles. Overall our study indicates the promise of including shape anisotropic particles such as microflakes in battery electrodes.<br
Keywords: Particle coating; Formulation; Deposition; Battery electrode; Electrochemistry